The development of executive functions in high-level female soccer players - Beavan, A.; Spielmann, J.; Ehmann, P.; Mayer, J. (Perceptual and Motor Skills, 2022)
Executive functions (EFs) are higher-level cognitive functions that help keep an individual`s goal-oriented thoughts and actions aligned. While many studies have shown the importance of EFs in sport, a limitation in this literature is that female participants have been underrepresented. In this mixed-longitudinal study, we examined the development of EFs in a cohort of high performing female athletes. We collected data over five seasons in a large sample of 175 female soccer players (aged 12-29 years old) from the U14 - senior age groups of a professional German soccer club. Players undertook a large battery of cognitive tasks aimed at measuring higher-level cognitive functioning: a sustained attention task, a stop-signal task, a Go-No-go test, an N-Back Test, and both a 180°- and 360°-multiple-object tracking task. We used linear and non-linear mixed effect regressions to examine the relationship between age and EFs. Second order polynomial curves explained many of these relationships between age and EFs compared to their linear relationships. Negatively accelerated curves reveal that these players` cognitive abilities mainly developed before players reached early adulthood, with a performance plateau evident at around 21 years of age. Age explained low to moderate proportions of the variance in EFs (<1-50%), while cognitive development across playing positions was not a strong contributor to this variance (M = 2.1, SD = 2.1%). We concluded that age has a negatively accelerated relationship with EFs in female soccer players that does not differ between playing positions. These data support the idea that athletes require only a reasonable level of EF ability to perform at the highest level of their sport. Our research raises new questions regarding the validity of current EF measurement methods for inferring information about in-game use of these cognitive abilities.